Involvement of RpoN in Regulating Motility, Biofilm, Resistance, and Spoilage Potential of Pseudomonas fluorescens - Liu, Xiaoxiang; Ye, Yifan; Zhu, Yin; Wang, Lifang; Yuan, Leyang; Zhu, Junli; Sun, Aihua (Frontiers in Microbiology, 2021)
Pseudomonas fluorescens is a typical spoiler of proteinaceous foods, and it is characterized by high spoilage activity. The sigma factor RpoN is a well-known regulator controlling nitrogen assimilation and virulence in many pathogens. However, its exact role in regulating the spoilage caused by P. fluorescens is unknown. Here, an in-frame deletion mutation of rpoN was constructed to investigate its global regulatory function through phenotypic and RNA-seq analysis. The results of phenotypic assays showed that the rpoN mutant was deficient in swimming motility, biofilm formation, and resistance to heat and nine antibiotics, while the mutant increased the resistance to H2O2. Moreover, the rpoN mutant markedly reduced extracellular protease and total volatile basic nitrogen (TVB-N) production in sterilized fish juice at 4℃; meanwhile, the juice with the rpoN mutant showed significantly higher sensory scores than that with the wild-type strain. To identify RpoN-controlled genes, RNA-seq-dependent transcriptomics analysis of the wild-type strain and the rpoN mutant was performed. A total of 1224 genes were significantly downregulated, and 474 genes were significantly upregulated by at least two folds at the RNA level in the rpoN mutant compared with the wild-type strain, revealing the involvement of RpoN in several cellular processes, mainly flagellar mobility, adhesion, polysaccharide metabolism, resistance, amino acid transport, and metabolism; this may contribute to the swimming motility, biofilm formation, stress and antibiotic resistance, and spoilage activities of P. fluorescens. Our results provide insights into the regulatory role of RpoN of P. fluorescens in food spoilage, which can be valuable to ensure food quality and safety.